2015
DOI: 10.1002/jsfa.7442
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical and microbiological characterisation of Italian fermented sausages in relation to their size

Abstract: In spite of the extreme variability of the sausage types at the end of ripening, this work showed that it was possible to find a strict relationship between sausages diameter and some essential physico-chemical parameters. Thus, the cross-sectional size of the product is an essential parameter, which can drive the biochemical processes during ripening, not only by affecting the kinetics of water losses, but also by influencing the microbiota enzymatic activity. © 2015 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 45 publications
(83 reference statements)
1
4
0
Order By: Relevance
“…Similar results were reported by Komprda et al [ 46 ] in typical Czech sausages and by Latorre-Moratalla [ 47 ] in fuet and llonganissa. In Italian salami, a similar trend was observed by Anastasio et al [ 19 ] and, recently, Tabanelli et al [ 21 ] found that BA amounts could be related to the size of sausages with the larger diameter including a higher concentration. The lower BA level in small size sausages can be attributed to the shorter ripening time and, consequently, to the time needed to reach a w values able to inhibit the metabolism of decarboxylating microorganisms and/or the action of decarboxylases.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Similar results were reported by Komprda et al [ 46 ] in typical Czech sausages and by Latorre-Moratalla [ 47 ] in fuet and llonganissa. In Italian salami, a similar trend was observed by Anastasio et al [ 19 ] and, recently, Tabanelli et al [ 21 ] found that BA amounts could be related to the size of sausages with the larger diameter including a higher concentration. The lower BA level in small size sausages can be attributed to the shorter ripening time and, consequently, to the time needed to reach a w values able to inhibit the metabolism of decarboxylating microorganisms and/or the action of decarboxylases.…”
Section: Discussionsupporting
confidence: 82%
“…It has been reported that sausage diameter plays a relevant role in the formation of the desired characteristics. In fact, it affects many important events during ripening such as the removal of water and the presence of oxygen inside the sausage, which, in turn, influence the biochemical activities of this crucial period [ 19 , 20 , 21 ]. Recently, some authors applied a linear discriminant analysis to highlight the role of diameter on the aroma profile and chemico-physical characteristics of different Italian industrial fermented sausages typologies [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…At the beginning of the process, total mesophilic bacteria (TMB) and lactic acid bacteria (LAB) had mean counts of 6.8 and 5.8 log cfu/g respectively, in accordance with the amount of starter inoculated. In summary, microbial counts in control samples were in the range expected and followed the dynamics observed in slow fermented sausages (Rantsiou et al, 2005;Samelis et al, 1998, Di Luccia et al, 2016, Tabanelli et al, 2016. Hospital et al (2015) studied the effect of nitrate and nitrite reduction on the microbial growth of dry fermented sausages.…”
Section: Microbiological Analysesmentioning
confidence: 63%
“…GC-MS can be used in several fields, such as plant metabolomics, as reported by Stashenko et al ( 2004 ), who used SPME-GC-MS for sampling the volatile plant metabolites, or for example, by Akhatou et al ( 2016 ), who combined GC-MS with multivariate statistical techniques to characterize the primary metabolome of different strawberry cultivars, and to study the influence of multiple agronomic conditions. Moreover, as reported by Currie et al ( 2016 ), GC-MS has proved useful in microbial metabolomics related to pharmaceutical studies to analyze the endogenous metabolite levels produced by Pseudomonas putida in response to six pharmaceuticals; or in food studies, when used to characterize the microbial metabolite production in: cheese (Vannini et al, 2008 ; Pisano et al, 2016 ), probiotic food (Patrignani et al, 2009 ; Tabanelli et al, 2015b ), sourdough (Guerzoni et al, 2007 ), wine (Vernocchi et al, 2011 ; Patrignani et al, 2016 ), sausages (Tabanelli et al, 2015a ), and ready to eat products (Siroli et al, 2015 ). Moreover, GC-MS is used in clinical applications, for example to analyze volatile compounds (SPME-GC-MS) in urine, blood, feces, hair, breath and saliva (Mills and Walker, 2001 ), or to evaluate biomarkers in several diseases, such as asthma (Gahleitner et al, 2013 ; Chang et al, 2015 ), schizophrenia (Liu et al, 2010 ), depressive disorders (Ding et al, 2014 ), ulcerative colitis (Kohashi et al, 2014 ), and neonatal sepsis (Fanos et al, 2014 ).…”
Section: Volatile and Non-volatile Compounds: Detection Methods And Dmentioning
confidence: 99%